How to find g(x) and aux function h(x) when doing fixed point interation?
$begingroup$
I'm learning fixed point iteration (first and second form).
My teacher said there are two forms:
g(x) = x - f(x)
g(x) = x - h(x)f(x)
where h(x)
is an aux function.
suppose f(x) = x^2 + 2x -3
.
Let f(x) = 0
.
x^2 + 2x -3 = 0
x^2 = - 2x + 3
x = 3/x -2
So we let g(x) = 3/x -2
, for a fixed point, and root, right?
To solve, we iterate and see convergence:
xk+1 = 3/xk -2
and pick an initial xk
.
My teacher said that in second form:
from f(x) = x^2 + 2x -3
:
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux function h(x) = -1 / (x^2 - 5)
Where did he get h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
from?
thanks!
fixed-point-theorems fixedpoints
$endgroup$
add a comment |
$begingroup$
I'm learning fixed point iteration (first and second form).
My teacher said there are two forms:
g(x) = x - f(x)
g(x) = x - h(x)f(x)
where h(x)
is an aux function.
suppose f(x) = x^2 + 2x -3
.
Let f(x) = 0
.
x^2 + 2x -3 = 0
x^2 = - 2x + 3
x = 3/x -2
So we let g(x) = 3/x -2
, for a fixed point, and root, right?
To solve, we iterate and see convergence:
xk+1 = 3/xk -2
and pick an initial xk
.
My teacher said that in second form:
from f(x) = x^2 + 2x -3
:
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux function h(x) = -1 / (x^2 - 5)
Where did he get h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
from?
thanks!
fixed-point-theorems fixedpoints
$endgroup$
add a comment |
$begingroup$
I'm learning fixed point iteration (first and second form).
My teacher said there are two forms:
g(x) = x - f(x)
g(x) = x - h(x)f(x)
where h(x)
is an aux function.
suppose f(x) = x^2 + 2x -3
.
Let f(x) = 0
.
x^2 + 2x -3 = 0
x^2 = - 2x + 3
x = 3/x -2
So we let g(x) = 3/x -2
, for a fixed point, and root, right?
To solve, we iterate and see convergence:
xk+1 = 3/xk -2
and pick an initial xk
.
My teacher said that in second form:
from f(x) = x^2 + 2x -3
:
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux function h(x) = -1 / (x^2 - 5)
Where did he get h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
from?
thanks!
fixed-point-theorems fixedpoints
$endgroup$
I'm learning fixed point iteration (first and second form).
My teacher said there are two forms:
g(x) = x - f(x)
g(x) = x - h(x)f(x)
where h(x)
is an aux function.
suppose f(x) = x^2 + 2x -3
.
Let f(x) = 0
.
x^2 + 2x -3 = 0
x^2 = - 2x + 3
x = 3/x -2
So we let g(x) = 3/x -2
, for a fixed point, and root, right?
To solve, we iterate and see convergence:
xk+1 = 3/xk -2
and pick an initial xk
.
My teacher said that in second form:
from f(x) = x^2 + 2x -3
:
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux function h(x) = -1 / (x^2 - 5)
Where did he get h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
from?
thanks!
fixed-point-theorems fixedpoints
fixed-point-theorems fixedpoints
asked Dec 13 '18 at 17:20
Jay PatelJay Patel
656
656
add a comment |
add a comment |
1 Answer
1
active
oldest
votes
$begingroup$
My teacher said that in second form: from
f(x) = x^2 + 2x -3
:
[one could consider]
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux[iliary] function
h(x) = -1 / (x^2 - 5)
Where did he get
h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
[coming] from?
This is most probably not what they said, and it seems that typos due to carelessness are killing you here.
Actually, to solve $f(x)=0$ with $f(x)=x^2 + 2x -3$, they most probably suggested to solve $g(x)=x$ with $$g(x) = x + frac{x^2 + 2x -3}{x^2 - 5}$$ that is, a function $g$ exactly of the general form $g(x)=x-f(x)h(x)$, for the auxiliary function $$h(x) = -frac1{x^2 - 5}$$ They chose $h$ arbitrarily.
Supplementary material: This choice of auxiliary function $h$ is not especially suited to this precise function $f$, if you ask me. A better choice would be to get rid of the $x^2$ term in $f(x)$, using $$g_c(x)=x-frac{x^2 + 2x -3}{x+c}$$ for some fixed positive $c$, that is, $g_c(x)=x-f(x)h_c(x)$ with $$h_c(x)=frac1{x+c}$$ Now, a simple computation shows that $$g_c(x)=frac{(c-2)x+3}{x+c}$$ hence the value $c=2$ is interesting, leading to the iteration of the function $$g_2(x)=frac3{x+2}$$
Note finally that for every initial condition $x_0geqslant0$, the sequence defined recursively by $x_{n+1}=g_2(x_n)$ converges to the positive root $x^*$ of $f$ at a geometric rate $frac13$ (and that $x^*=1$, but this is irrelevant to the construction and to the remark).
$endgroup$
add a comment |
Your Answer
StackExchange.ifUsing("editor", function () {
return StackExchange.using("mathjaxEditing", function () {
StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix) {
StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
});
});
}, "mathjax-editing");
StackExchange.ready(function() {
var channelOptions = {
tags: "".split(" "),
id: "69"
};
initTagRenderer("".split(" "), "".split(" "), channelOptions);
StackExchange.using("externalEditor", function() {
// Have to fire editor after snippets, if snippets enabled
if (StackExchange.settings.snippets.snippetsEnabled) {
StackExchange.using("snippets", function() {
createEditor();
});
}
else {
createEditor();
}
});
function createEditor() {
StackExchange.prepareEditor({
heartbeatType: 'answer',
autoActivateHeartbeat: false,
convertImagesToLinks: true,
noModals: true,
showLowRepImageUploadWarning: true,
reputationToPostImages: 10,
bindNavPrevention: true,
postfix: "",
imageUploader: {
brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
allowUrls: true
},
noCode: true, onDemand: true,
discardSelector: ".discard-answer"
,immediatelyShowMarkdownHelp:true
});
}
});
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3038327%2fhow-to-find-gx-and-aux-function-hx-when-doing-fixed-point-interation%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
1 Answer
1
active
oldest
votes
1 Answer
1
active
oldest
votes
active
oldest
votes
active
oldest
votes
$begingroup$
My teacher said that in second form: from
f(x) = x^2 + 2x -3
:
[one could consider]
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux[iliary] function
h(x) = -1 / (x^2 - 5)
Where did he get
h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
[coming] from?
This is most probably not what they said, and it seems that typos due to carelessness are killing you here.
Actually, to solve $f(x)=0$ with $f(x)=x^2 + 2x -3$, they most probably suggested to solve $g(x)=x$ with $$g(x) = x + frac{x^2 + 2x -3}{x^2 - 5}$$ that is, a function $g$ exactly of the general form $g(x)=x-f(x)h(x)$, for the auxiliary function $$h(x) = -frac1{x^2 - 5}$$ They chose $h$ arbitrarily.
Supplementary material: This choice of auxiliary function $h$ is not especially suited to this precise function $f$, if you ask me. A better choice would be to get rid of the $x^2$ term in $f(x)$, using $$g_c(x)=x-frac{x^2 + 2x -3}{x+c}$$ for some fixed positive $c$, that is, $g_c(x)=x-f(x)h_c(x)$ with $$h_c(x)=frac1{x+c}$$ Now, a simple computation shows that $$g_c(x)=frac{(c-2)x+3}{x+c}$$ hence the value $c=2$ is interesting, leading to the iteration of the function $$g_2(x)=frac3{x+2}$$
Note finally that for every initial condition $x_0geqslant0$, the sequence defined recursively by $x_{n+1}=g_2(x_n)$ converges to the positive root $x^*$ of $f$ at a geometric rate $frac13$ (and that $x^*=1$, but this is irrelevant to the construction and to the remark).
$endgroup$
add a comment |
$begingroup$
My teacher said that in second form: from
f(x) = x^2 + 2x -3
:
[one could consider]
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux[iliary] function
h(x) = -1 / (x^2 - 5)
Where did he get
h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
[coming] from?
This is most probably not what they said, and it seems that typos due to carelessness are killing you here.
Actually, to solve $f(x)=0$ with $f(x)=x^2 + 2x -3$, they most probably suggested to solve $g(x)=x$ with $$g(x) = x + frac{x^2 + 2x -3}{x^2 - 5}$$ that is, a function $g$ exactly of the general form $g(x)=x-f(x)h(x)$, for the auxiliary function $$h(x) = -frac1{x^2 - 5}$$ They chose $h$ arbitrarily.
Supplementary material: This choice of auxiliary function $h$ is not especially suited to this precise function $f$, if you ask me. A better choice would be to get rid of the $x^2$ term in $f(x)$, using $$g_c(x)=x-frac{x^2 + 2x -3}{x+c}$$ for some fixed positive $c$, that is, $g_c(x)=x-f(x)h_c(x)$ with $$h_c(x)=frac1{x+c}$$ Now, a simple computation shows that $$g_c(x)=frac{(c-2)x+3}{x+c}$$ hence the value $c=2$ is interesting, leading to the iteration of the function $$g_2(x)=frac3{x+2}$$
Note finally that for every initial condition $x_0geqslant0$, the sequence defined recursively by $x_{n+1}=g_2(x_n)$ converges to the positive root $x^*$ of $f$ at a geometric rate $frac13$ (and that $x^*=1$, but this is irrelevant to the construction and to the remark).
$endgroup$
add a comment |
$begingroup$
My teacher said that in second form: from
f(x) = x^2 + 2x -3
:
[one could consider]
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux[iliary] function
h(x) = -1 / (x^2 - 5)
Where did he get
h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
[coming] from?
This is most probably not what they said, and it seems that typos due to carelessness are killing you here.
Actually, to solve $f(x)=0$ with $f(x)=x^2 + 2x -3$, they most probably suggested to solve $g(x)=x$ with $$g(x) = x + frac{x^2 + 2x -3}{x^2 - 5}$$ that is, a function $g$ exactly of the general form $g(x)=x-f(x)h(x)$, for the auxiliary function $$h(x) = -frac1{x^2 - 5}$$ They chose $h$ arbitrarily.
Supplementary material: This choice of auxiliary function $h$ is not especially suited to this precise function $f$, if you ask me. A better choice would be to get rid of the $x^2$ term in $f(x)$, using $$g_c(x)=x-frac{x^2 + 2x -3}{x+c}$$ for some fixed positive $c$, that is, $g_c(x)=x-f(x)h_c(x)$ with $$h_c(x)=frac1{x+c}$$ Now, a simple computation shows that $$g_c(x)=frac{(c-2)x+3}{x+c}$$ hence the value $c=2$ is interesting, leading to the iteration of the function $$g_2(x)=frac3{x+2}$$
Note finally that for every initial condition $x_0geqslant0$, the sequence defined recursively by $x_{n+1}=g_2(x_n)$ converges to the positive root $x^*$ of $f$ at a geometric rate $frac13$ (and that $x^*=1$, but this is irrelevant to the construction and to the remark).
$endgroup$
My teacher said that in second form: from
f(x) = x^2 + 2x -3
:
[one could consider]
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
with the aux[iliary] function
h(x) = -1 / (x^2 - 5)
Where did he get
h(x) = -1 / (x^2 - 5)
from? And where is
g(x) = (x + (x^2 + 2x -3)) / (x^2 - 5)
[coming] from?
This is most probably not what they said, and it seems that typos due to carelessness are killing you here.
Actually, to solve $f(x)=0$ with $f(x)=x^2 + 2x -3$, they most probably suggested to solve $g(x)=x$ with $$g(x) = x + frac{x^2 + 2x -3}{x^2 - 5}$$ that is, a function $g$ exactly of the general form $g(x)=x-f(x)h(x)$, for the auxiliary function $$h(x) = -frac1{x^2 - 5}$$ They chose $h$ arbitrarily.
Supplementary material: This choice of auxiliary function $h$ is not especially suited to this precise function $f$, if you ask me. A better choice would be to get rid of the $x^2$ term in $f(x)$, using $$g_c(x)=x-frac{x^2 + 2x -3}{x+c}$$ for some fixed positive $c$, that is, $g_c(x)=x-f(x)h_c(x)$ with $$h_c(x)=frac1{x+c}$$ Now, a simple computation shows that $$g_c(x)=frac{(c-2)x+3}{x+c}$$ hence the value $c=2$ is interesting, leading to the iteration of the function $$g_2(x)=frac3{x+2}$$
Note finally that for every initial condition $x_0geqslant0$, the sequence defined recursively by $x_{n+1}=g_2(x_n)$ converges to the positive root $x^*$ of $f$ at a geometric rate $frac13$ (and that $x^*=1$, but this is irrelevant to the construction and to the remark).
answered Dec 21 '18 at 10:49
DidDid
248k23223460
248k23223460
add a comment |
add a comment |
Thanks for contributing an answer to Mathematics Stack Exchange!
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
Use MathJax to format equations. MathJax reference.
To learn more, see our tips on writing great answers.
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3038327%2fhow-to-find-gx-and-aux-function-hx-when-doing-fixed-point-interation%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown